Management of epithelial ovarian cancer at a tertiary centre in South Africa: a retrospective evaluation of early recurrence and contributory factors - Gimei, Peter (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPhil)--Stellenbosch University, 2019.